Encouragement of the Personnel of the State Labor Service of Ukraine to Implement International Experience within Labor Protection Management (Law and Safety, 2021)
The subject matter of the research of the motives of state officials are socio-economic and legal relations that arise in the process of improving the activities of the State Labor Service of Ukraine (SLS) in the field of “Labor Protection”. The object of the research is the system of state management of labor protection and technology of personnel incentives in the regional departments of the SLS. The purpose of the work is theoretical substantiation and development of recommendations for improving the activities and increasing motivation of the staff of the SLS of Ukraine in Sumy region, in particular the implementation of the experience of advanced world countries into the management strategies. Implementation of the current regulatory base in the field of labor protection in Ukraine, in accordance with international requirements, requires high qualification and motivation of the staff of the relevant executive authorities, the development of effective tools to stimulate the efficient work of those state officials.The authors have studied the role and place of the SLS of Ukraine regarding the adaptation and implementation of the experience of advanced world countries into the management strategies of labor protection defined in the Conventions of the International Labor Organization and the Directives of the European Union. The authors have determined the subjects of influence in the field of protection of labor rights, labor protection, preservation of life and health of the participants in the production process, in particular the executive authorities of public administration and the Federation of Trade Unions of Ukraine. The authors have developed suggestions on encouraging the staff of the SLS to implement high-quality international labor protection standards on the basis of motivational profiles and their monitoring. Ukraine has chosen an effective model of supervision and control over the compliance with labor legislation. The advantage of this model is the ability of inspections to delegate their powers from central authorities to local agencies.The conducted study is of theoretical and practical interest in regard to the systems of labor inspections in different countries, it allows us to determine the place of national government in the overall system of such inspections. The results of the research can be recommended for implementation in public administration and local self-government agencies in the field of labor protection in Ukraine.
Keywords: labor protection; system; regulatory acts; state service; labor conditions; a trade union; public control; encouragement of the personnel; motivational profiles; motivational monitoring; incentive payments; bonuses